A Comprehensive Study on Mechanical Properties of Nominal Grade Concrete Using Copper Slag as Partial Replacement to Fine Aggregate - J, USHAKRANTI; K, SRINIVASU; SAI, NAGA (International Journal of Engineering and Technology, 2018)
Currently situation, improvement of infrastructure has created an excessive demand for herbal sand, which makes it greater expensive and leads to environmental imbalances. The utilization of suitable sustainable choice materials proves that it is the most efficacious choice to traditional concrete materials and can take care of the surrounding environment. Copper slag is an industrial byproduct of copper production. Copper slag is a high-gravity glassy granular material. This paper reports some experimental studies on the outcome of partially changed sand from impact of copper slag on the mechanical houses of concrete. M30 concrete adopts copper slag plan and partly substitutes high-quality combination fines by means of 0%, 10%, 20%, 30%, 40%, 50%, 60%, 80% and 100%. The mechanical properties of concrete measured in the laboratory encompass compressive strength, split tensile strength and bending tensile strength. The have an impact on of partly replacing the quality aggregates with copper slag on the compressive strength, the cut up tensile power of the cylinder and the bending power of the prism has been evaluated. Water absorption assessments have been also conducted to report the impact of copper slag on the absorption price of concrete. Test results affords that it is feasible to utilize copper slag as best aggregate in concrete.Â